2009
DOI: 10.1371/journal.pone.0006497
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Prion Protein Interacts with the Tissue Non-Specific Alkaline Phosphatase in Membrane Microdomains of Bioaminergic Neuronal Cells

Abstract: BackgroundThe cellular prion protein, PrPC, is GPI anchored and abundant in lipid rafts. The absolute requirement of PrPC in neurodegeneration associated to prion diseases is well established. However, the function of this ubiquitous protein is still puzzling. Our previous work using the 1C11 neuronal model, provided evidence that PrPC acts as a cell surface receptor. Besides a ubiquitous signaling function of PrPC, we have described a neuronal specificity pointing to a role of PrPC in neuronal homeostasis. 1C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…Furthermore, intestinal AP has been implicated in fatty acid transport in enterocytes [463]. Moreover, AP can dephosphorylate extracellular proteins at physiological pH [508][509][510][511][512][513]. Calf IAP is widely used in molecular biology to dephosphorylate nucleic acids.…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, intestinal AP has been implicated in fatty acid transport in enterocytes [463]. Moreover, AP can dephosphorylate extracellular proteins at physiological pH [508][509][510][511][512][513]. Calf IAP is widely used in molecular biology to dephosphorylate nucleic acids.…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 99%
“…This interaction takes place in lipid rafts of cultured neuroepithelial cell lines (1C11) that can be differentiated towards a serotonergic (1C11 5-HT ) or noradrenergic (1C11 NE ) phenotype. Since TNAP can dephosphorylate laminin, it is hypothesized that TNAP acts as a functional protagonist in the PrP C interplay [511].…”
Section: Protein Interactionsmentioning
confidence: 99%
“…On the other hand, neuronal cells and BCECs exclusively express the bone TNAP transcript in human, marmoset, rat and mouse. In fine, TNAP is the only AP isoform found in the brain (Ermonval et al 2009). This characteristic was also noted in several in vitro models of mammalian BBBs (Meyer et al 1990;Nakazato et al 1997;Sobue et al 1999).…”
Section: Ap Activity: a Very Useful Marker Of The Bbb Phenotypementioning
confidence: 99%
“…However, despite its known phosphomonoesterase activity, TNAP's putative ability to dephosphorylate protein targets remains subject to debate. Direct proof of TNAP's action on the phosphorylation state of laminin has been reported (Ermonval et al 2009) but contrasts with evidence to show that TNAP does not modulate the phosphorylation of plasma membrane proteins (Fedde et al 1993). In Alzheimer's disease (AD), hyperphosphorylation of the tau protein plays a key role in progression of AD.…”
Section: Ap Activity: a Very Useful Marker Of The Bbb Phenotypementioning
confidence: 99%
“…Indeed, although early studies (Landow et al 1942;Bourne 1943) did not report AP activity at the neuronal level in mammals-except in the spinal cord and medulla -, later studies demonstrated significant AP activity in multiple brain structures of various mammalian species. The pharmacological profile of this neuronal AP activity suggested it resulted from TNAP activity (Fonta et al 2004;Langer et al 2008) and it has recently been formally ascribed to TNAP gene expression (Ermonval et al 2009;Brun-Heath et al 2011).…”
Section: Introductionmentioning
confidence: 95%